Protecția diplomatică și consulară a persoanei fizice prin prisma jurisprudenței CIJ [Articol] - Şiman, Corina (CEP USM, 2016)
Although the individual is not a subject of international law, his rights may be infringed on the international arena. In this regard, the intervention of diplomatic and consular protection is appropriate, and so as the exercise of diplomatic asylum. These are different institutions of international law that mustn’t be confounded, and their thorough understanding is possible through the analysis of the jurisprudence of the International Court of Justice.
Keywords: protecția diplomatică; protecția consulară